2020
DOI: 10.3389/fspor.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Player Monitoring in Professional Soccer: Spikes in Acute:Chronic Workload Are Dissociated From Injury Occurrence

Abstract: This study aimed to determine whether spikes in acute:chronic workload ratio (ACWR) are associated with injury incidence, and to examine the differences in external load due to greater or lesser exposure to matches and the long-term effects of the load during a chronic seasonal period. Fifteen professional soccer players belonging to the squad of a European Champions League club were enrolled in this study. External training and match load were assessed from all athletes using a global positioning system (GPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Differences in participation in official games, as in our second studied season, can cause significant imbalances in the chronic external loads between players in a team [45]. This situation should be considered and minimised in training sessions to prevent imbalances in workload for those who usually play or not.…”
Section: Discussionmentioning
confidence: 88%
“…Differences in participation in official games, as in our second studied season, can cause significant imbalances in the chronic external loads between players in a team [45]. This situation should be considered and minimised in training sessions to prevent imbalances in workload for those who usually play or not.…”
Section: Discussionmentioning
confidence: 88%
“…Although the method provides several practical metrics, the reliability and validity of the method will significantly be affected by individual differences and the training load quantification method. For instance, Gabbett et al (2016) found an association between exponentially weighted moving averages of training load and injury risk that was not found in some research ( Suárez-Arrones et al, 2020 ). It is important to note that most studies use a single evaluation method to quantify training loads, such as distance, session RPE, and other indicators, which may lead to statistical indicators of training load associated with injury risk that are not personalized.…”
Section: Discussionmentioning
confidence: 93%
“…Identifying potential risk factors for sports injuries through training load monitoring and timely adjustment of the training program is vital for developing injury prevention strategies ( Schwellnus et al, 2016 ; Soligard et al, 2016 ). Although there is much research evidence that excessive or sudden increases in training load are an important cause of injury ( Gabbett, 2016 ; Gabbett et al, 2016 ), these phenomena were not found in the research reports by Suárez-Arrones et al (2020) . These conflicting research findings hinder the development of injury prevention strategies based on load management.…”
Section: Introductionmentioning
confidence: 98%
“…These high scores may be associated with disease incidence, poor performance, and the onset of overtraining [36,38]. With this, the use of the ACWR to understand changes in the load and how these changes relate to risk of injur, has received increasing scientific attention [41,42]. ACWR is calculated by dividing the AWL (the workload of the week preceding the injury, fatigue component) by the CWL (the aver-age workload of the four weeks preceding the injury, fitness component) [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…With this, the use of the ACWR to understand changes in the load and how these changes relate to risk of injur, has received increasing scientific attention [41,42]. ACWR is calculated by dividing the AWL (the workload of the week preceding the injury, fatigue component) by the CWL (the aver-age workload of the four weeks preceding the injury, fitness component) [41,42]. Considering the training intensity parameters mentioned above, coaches can determine the physical and physiological effects of training sessions on players.…”
Section: Introductionmentioning
confidence: 99%